Characteristics of pollen morphology and viability of four species of Magnolia - Normasiwi, Suluh; Kurniawati, Feby (Buletin Kebun Raya, 2023)
Magnolia is a primitive flower plant with attractive colors and has its uniqueness. Several studies of Magnolia reproduction biology have been carried out, including a pollen study. Magnolia pollen has a long fossil record and the most primitive morphology, making it interesting to study further. In addition, knowledge of pollen quality is essential in developing Magnolia cultivation to predict plant reproductive ability as part of hybridization studies. The research aimed to determine the characteristics of differences in morphology and pollen viability of four Magnolia species, namely M. champaca, M. grandiflora, M. liliifera, and M. obovata. The observation of pollen morphology was done using Scanning Electron Microscope. Pollen viability was tested with two methods, i.e., staining (I2KI 1%, Orcein 2%, and TTC 1%) and in vitro germination (5 ppm boric acid and 5%, 10%, 15%, and 20% sucrose). The results showed that the four Magnolia species had almost identical morphology and uniqueness. The largest pollen size was M. grandiflora, while the smallest was M. champaca. Furthermore, the staining test using the I2KI solution had higher pollen viability value than orcein and TTC. On in vitro germination test, only M. grandiflora pollen could be germinated in media of 5% boric acid + sucrose at a temperature of 4℃.